1996
DOI: 10.1128/jvi.70.12.8355-8360.1996
|View full text |Cite
|
Sign up to set email alerts
|

Primary, syncytium-inducing human immunodeficiency virus type 1 isolates are dual-tropic and most can use either Lestr or CCR5 as coreceptors for virus entry

Abstract: A panel of primary syncytium-inducing (SI) human immunodeficiency virus type 1 isolates that infected several CD4 ؉ T-cell lines, including MT-2 and C8166, were tested for infection of blood-derived macrophages. Infectivity titers for C8166 cells and macrophages demonstrated that primary SI strains infected macrophages much more efficiently than T-cell line-adapted HIV-1 strains such as LAI and RF. These primary SI strains were therefore dual-tropic. Nine biological clones of two SI strains, prepared by limiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
153
0
3

Year Published

1998
1998
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 342 publications
(167 citation statements)
references
References 40 publications
11
153
0
3
Order By: Relevance
“…Five major chemokine receptor classes (CC, CXC, CC/CXC, C, and CX 3 C) have been classified and 15 chemokine receptor subtypes within these five groups have been identified. Among the CC and CXC families are CCR5 and CXCR4, the principal coreceptors for entry of M-tropic (R5) and T-tropic (X4) HIV-1 virus into macrophages and T lymphocytes, respectively (8,26,27). The natural ligand for CXCR4, SDF-1␣ (CXCL12), was identified and found to be highly expressed in fetal liver and bone marrow stromal cells (5,25,28).…”
Section: Discussionmentioning
confidence: 99%
“…Five major chemokine receptor classes (CC, CXC, CC/CXC, C, and CX 3 C) have been classified and 15 chemokine receptor subtypes within these five groups have been identified. Among the CC and CXC families are CCR5 and CXCR4, the principal coreceptors for entry of M-tropic (R5) and T-tropic (X4) HIV-1 virus into macrophages and T lymphocytes, respectively (8,26,27). The natural ligand for CXCR4, SDF-1␣ (CXCL12), was identified and found to be highly expressed in fetal liver and bone marrow stromal cells (5,25,28).…”
Section: Discussionmentioning
confidence: 99%
“…Complicating any interpretation is the demonstration that R5 simian immunodeficiency virus (SIV) strains are certainly pathogenic and lethal without the X4 transition (as R5 HIV strains can be in people); SIV strains can actually increase their virulence over the course of infection without any switch in co-receptor usage (56). A clear rationale for the R5-X4 transition remains elusive, although the remarkable transition in tropism in a significant subset of individuals is firmly established (23)(24)(25)(26).…”
Section: The Ccr5-32 Variant and Aidsmentioning
confidence: 99%
“…SIV is endemic among several small African monkey species, including mangabeys, and is thought to represent the origin of HIV-2, a phylogenetically divergent and less virulent strain of the AIDS virus which is restricted to west Africa (82). Genotypic sampling of the red capped mangabey revealed the presence of a CCR5 receptorinactivating ,24 deletion mutation with a frequency of 87%, meaning that 98% of individuals carried at least one copy of CCR5-, 24. SIV isolates from other monkey species all use CCR5, but the red capped mangabey SIV isolate does not; its primary entry receptor is CCR2.…”
Section: Fig 2 Diagram Of a Ccr Molecule Spanning A Cell Membrane Wmentioning
confidence: 99%
See 1 more Smart Citation
“…Transmission studies have shown that the initial infection is almost invariably established by NSI/ M-tropic strains. Thus, primary HIV-1 strains of the NSI type often use the CCR-5 coreceptor to gain entry in macrophage/ monocyte cell lines [18]. Strains, which rely on a broader range of coreceptors, may develop during the course of infection [19].…”
Section: Hiv Tropism and Entrymentioning
confidence: 99%